Fear of Service Outsourcing : Is It Justified? - Amiti, Mary (IMF Working Papers; Working Paper ;, 2004)
The recent media and political attention on service outsourcing from developed to developing countries gives the impression that outsourcing is exploding. As a result, workers in industrial countries are anxious about job losses. This paper aims to establish what are the hypes and what are the facts. The results show that although service outsourcing has been steadily increasing it is still very low, and that in the United States and many other industrial countries "insourcing" is greater than outsourcing. Using the United Kingdom as a case study, we find that job growth at a sectoral level is not negatively related to service outsourcing.